2018
DOI: 10.1186/s12864-018-5061-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling associated with muscle growth in modern broilers compared to an unselected chicken breed

Abstract: BackgroundGenetically selected modern broiler chickens have acquired outstanding production efficiency through rapid growth and improved feed efficiency compared to unselected chicken breeds. Recently, we analyzed the transcriptome of breast muscle tissues obtained from modern pedigree male (PeM) broilers (rapid growth and higher efficiency) and foundational Barred Plymouth Rock (BPR) chickens (slow growth and poorer efficiency). This study was designed to investigate microRNAs that play role in rapid growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Furthermore, interest in this transcription factor goes beyond stress. For example, when a comparison of a single male modern broiler line compared to a foundational Barred Plymouth Rock chicken line was conducted, it showed that Nrf2 expression in breast muscle was much higher in the modern broiler compared to the foundational BPR line [299], and it was suggested Nrf2-mediated oxidative stress response pathways are involved in breast muscle growth in chickens [300]. In recent years, several compounds, including carnitine, have been shown to have inhibitory activities against multiple components of the NF-κB activation pathway.…”
Section: Other Nutrients and Probioticsmentioning
confidence: 99%
“…Furthermore, interest in this transcription factor goes beyond stress. For example, when a comparison of a single male modern broiler line compared to a foundational Barred Plymouth Rock chicken line was conducted, it showed that Nrf2 expression in breast muscle was much higher in the modern broiler compared to the foundational BPR line [299], and it was suggested Nrf2-mediated oxidative stress response pathways are involved in breast muscle growth in chickens [300]. In recent years, several compounds, including carnitine, have been shown to have inhibitory activities against multiple components of the NF-κB activation pathway.…”
Section: Other Nutrients and Probioticsmentioning
confidence: 99%
“…skeletal muscle differentiation and development [10][11][12] . Recent studies have shown that some muscle-specific miRNAs play an important role in the regulation of muscle fiber type specification and maintenance in certain vertebrate species 13,14 .…”
mentioning
confidence: 99%
“…Since this phenotype is similar to the sarcopenia phenotype, the authors speculate that miR-133a might have a significant role in maintaining skeletal muscle mitochondrial functionality. Other miRNAs, such as miR-340-5p and miR-206, have also been shown to regulate ROS generation in skeletal muscle via Nrf2, which is a key factor in regulating redox homeostasis, although the molecular mechanisms involved in its effect in the onset of sarcopenia are still unknown [ 153 , 154 ].…”
Section: Nutrition-dependent Microrna Regulation Of Mitochondrial mentioning
confidence: 99%